1985
DOI: 10.1002/ajmg.1320200115
|View full text |Cite
|
Sign up to set email alerts
|

Duplication of hands and feet, multiple joint dislocations, absence of corpus callosum and hypsarrhythmia: Acrocallosal syndrome?

Abstract: We describe a 14-month-old female infant with absence of corpus callosum, atrophy of optic nerve, peculiar face, complex polydactyly, multiple joint abnormalities, and femoral shortness. The similarities to and differences from previously reported cases of this kind suggest that our patient has a new type of acrocallosal syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

1988
1988
1997
1997

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…The similarity of the type of postaxial polydactyly of the left hand of our patient as shown in the radiograph (Fig. 5) to that shown in the case of Sanchis et al [1985] supports the view that their patient's limb anomaly only represents a quantitative difference. Our patient with an extra digit of one hand lies at one end of the spectrum, and their patient with high degrees of polydactyly is at the other end.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The similarity of the type of postaxial polydactyly of the left hand of our patient as shown in the radiograph (Fig. 5) to that shown in the case of Sanchis et al [1985] supports the view that their patient's limb anomaly only represents a quantitative difference. Our patient with an extra digit of one hand lies at one end of the spectrum, and their patient with high degrees of polydactyly is at the other end.…”
Section: Discussionsupporting
confidence: 84%
“…The hydrolethalus syndrome is further characterized by ossification defects of the skull, other midline defects, microphthalmia, congenital heart disease, severe hydrocephalus, preaxial polydactyly of the feet, and hydramnios. Sanchis et al [1985] reported a girl with craniofacial anomalies similar to those described in the acrocallosal syndrome associated with severe skeletal abnormalities, including high degrees of polydactyly of hands and feet. The similarity of the type of postaxial polydactyly of the left hand of our patient as shown in the radiograph (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…polydactyly [Sanchis et al, 1985;Philip et al, 1988;Schinzel, 1988;Temtamy and Meguid, 1989;Turolla et al, 1990;Yüksel et al, 1990;Gelman-Kohan et al, 1991;Christianson et al, 1994], and there is even one case [Guion-Almeida and Richieri-Costa, 1992] with neither pre-nor postaxial polydactyly clinically (but the radiographic findings do show a bifid distal phalanx at right and duplication at left). Various cardiac defects have been described: atrial septal defect [Schinzel, 1982;Christianson et al, 1994], dysplastic pulmonary valve [Moeschler et al, 1989], dextroposition of the aorta with an ostium secundum [Philip et al, 1988], tetralogy of Fallot [Casamassima et al, 1989], unusual configuration and position of both ventricles [Schinzel, 1979], VSD [Christianson et al, 1994].…”
Section: Fig 2 Agenesis Of the Corpus Callosum (Mri)mentioning
confidence: 95%
“…Autosomal recessive inheritance has been suggested [Schinzel and Kaufmann, 19861. Later reports [Nelson and Thomson, 1982;Schinzel, 1982a,b;Leguis et al, 1985;Sanchis et al, 1985;Toriello et al, 1986;Philip et al, 19881 expanded the phenotypic manifestations of the syndrome. Nelson and Thomson [1982] reported two unrelated patients.…”
Section: Discussionmentioning
confidence: 94%